Geomatics applications in monitoring light pollution "Baghdad Province as a Model" - Yahya Ahmed, Abeer (Journal of College of Education, 2021)
This study aims at (Geometrics application in monitoring light pollution "Baghdad Province as a model" to monitor this pollution from some visualization from global platforms (Map box), (light trends), (NOAA), (snap), (Horizon). It’s considered as a new category for measuring this measurement of pollution and its geographical distribution in Baghdad city, and mapping them with according to the varieties and their levels of dangerous and extracting by the program (Arc GIS( . The study has concluded that the rate of light pollution is connected in the capital city Baghdad. Due to the increasing population and varieties of land that increasing in nighttime illumination which affects human activities and other living organisms and the breaking through of Ecological balance.